Representações das mulheres cristãs-novas na historiografia de Anita Novinsky (1978-2007) - Barbosa, Isadora Regina Celso (2022)
The 16th century witnessed the emergence of the Old Colonial System, the rise of the Modern States, the artistic rise and religious reforms. However, despite all these “beauties”, this century saw the birth of the Iberian Inquisitions and the horror of the persecutions. Through denunciations and forging heresies, the Holy Inquisition had as its main target the New Christians and, with that, the Court of the Holy Office restricted individual liberties. The Catholic faith made the Inquisition one of the main institutions that maintained the Ancien Régime, giving absolute power to the clergy and the nobility over society. This process also reached the New World and had an impact on the political, cultural, religious, economic and social aspects of Brazil Colony. Having Jews converted to Christianity in the Iberian Peninsula as enemies during the 14th and 15th centuries, a portion of these individuals fled religious persecution to America and settled in Brazil. Within this historical context, the present theme of study is the historiographical production of Anita Novinsky's works, having as a cutout, among the various issues represented in the author's work, the New Christians, who were arrested and persecuted by the Inquisition in Brazil among the XVI to XIX centuries, present in the narrative of the following works of Anita Novinsky: Inquisition-Inventories of Confiscated Goods to New Christians in Brazil – century. XVIII (1978), Inquisition – Rol dos Culpados (1992), Inquisition – Prisoners of Brazil (XVI- XIX) (2002), and Office of Investigation: an unprecedented “hunt for Jews (2007), which are the source of study of this work. What we pose as a research problem are the historiographical narrative constructions of Novinsky, the sociocultural place of Christian- New European women, in the narrative about the past that give them representations that configure a social, historical and cultural identity, which will allow us to identify the identity design contextualizing the author and works in the Brazilian historiographical field, as well as her contribution to research and historical knowledge. We will use the disciplinary matrix of history as a method to enable reflection on the principles of historical science, proposed by Rüsen, which corresponds to the systematic interrelation of five factors, necessary, each for itself, and sufficient , as a whole, to organize historical knowledge as a cognitive process and, in the case of this research, for historiographical analysis. According to this assumption, the dissertation is structured in three chapters. In the first chapter, we contextualize the author and her historiographical work in the Brazilian historiographical field, as well as her contribution to research and knowledge, that is, we focused on surveying the author's biographical data, her historiographical motivations and her questions posed to the past. The second chapter aims to analyze and present the works; the narratives, protagonists and contexts covered. And, finally, in the third chapter we focus on the juxtaposition and relational comparison of the data, presented and analyzed in the second chapter, between the four works of the constituent elements narrated and identified individually, on which we analyze the representations and narrative forms elaborated on the Jewish women, guided by variables that constituted the questions formulated for the investigation.